Effects of lipids on the rate-limiting steps in the dark-to-light transition of Photosystem II core complex of Thermostichus vulcanus - Magyar, Melinda; Akhtar, Parveen; Sipka, Gábor; Domonkos, Ildikó; Han, Wenhui; Li, Xingyue; Han, Guangye; Shen, Jian-Ren; Lambrev, Petar H.; Garab, Győző (Frontiers in Plant Science, 2024)
In our earlier works, we have shown that the rate-limiting steps, associated with the dark-to-light transition of Photosystem II (PSII), reflecting the photochemical activity and structural dynamics of the reaction center complex, depend largely on the lipidic environment of the protein matrix. Using chlorophyll-a fluorescence transients (ChlF) elicited by single-turnover saturating flashes, it was shown that the half-waiting time (Δτ1/2) between consecutive excitations, at which 50% of the fluorescence increment was reached, was considerably larger in isolated PSII complexes of Thermostichus (T.) vulcanus than in the native thylakoid membrane (TM). Further, it was shown that the addition of a TM lipid extract shortened Δτ1/2 of isolated PSII, indicating that at least a fraction of the ‘missing’ lipid molecules, replaced by detergent molecules, caused the elongation of Δτ1/2. Here, we performed systematic experiments to obtain information on the nature of TM lipids that are capable of decreasing Δτ1/2. Our data show that while all lipid species shorten Δτ1/2, the negatively charged lipid phosphatidylglycerol appears to be the most efficient species – suggesting its prominent role in determining the structural dynamics of PSII reaction center.